2018
DOI: 10.1016/j.ijvsm.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the number of incisions and use of local anesthesia on the physiological indicators of surgically-castrated piglets

Abstract: The objective of this study was to determine the effect of local anesthesia and the number of incisions performed on the physiological blood profile of piglets after surgical castration. A total of 60 male piglets were divided into five groups of 12 each, based on the surgical method employed and the use, or not, of local anesthesia, as follows: surgical castration using one horizontal incision in both testicles with (C1+L) and without (C1) local anesthesia; surgical castration using two vertical scrotal incis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Several studies have already been conducted on local anesthesia as an alternative to piglet castration without anesthesia but they differed in study designs, local anesthetics used and yielded heterogeneous results [ 8 , 9 , 10 , 11 , 12 , 13 ]. This second part of a comprehensive study examined the four local anesthetics, procaine, lidocaine, bupivacaine and mepivacaine, in conscious piglets during castration in the first week of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have already been conducted on local anesthesia as an alternative to piglet castration without anesthesia but they differed in study designs, local anesthetics used and yielded heterogeneous results [ 8 , 9 , 10 , 11 , 12 , 13 ]. This second part of a comprehensive study examined the four local anesthetics, procaine, lidocaine, bupivacaine and mepivacaine, in conscious piglets during castration in the first week of life.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of castration with local anesthetics is currently not permitted in Germany, because the evidence of the efficacy of this method is still controversially discussed. Kluivers-Poodt et al [ 8 ], Hansson et al [ 9 ] and Leidig et al [ 10 ] concluded that the use of local anesthetics reduces pain responses during castration, whereas Perez-Pedraza et al [ 11 ] did not show any effect. Bonastre et al [ 12 ] as well as Rauh et al [ 13 ] indicated that local anesthetics lead to a reduction in pain-related responses, without eliminating the pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas different concentrations and application techniques of lidocaine [2,3,8,9,[15][16][17][18][19]21,39,41,[47][48][49][50][51][52][53][54][55][56] and procaine [9,17,41,42,[57][58][59] have been excessively studied in the context of piglet castration, bupivacaine was analyzed only in combination with lidocaine by Bonastre et al [60]. To the best of our knowledge, mepivacaine, an approved drug in several European countries for intraarticular and epidural injections in horses, has never been used in studies examining piglet castration.…”
Section: Plos Onementioning
confidence: 99%
“…The more consistent results are seen with the use of NSAIDs. Compared with piglets castrated without analgesic treatment, significantly reduced plasma cortisol and / or ACTH levels have been documented in NSAID-treated piglets at 30 mins [10,14,17,53] 60 min [13,23,24], or up to 4 hrs post-procedure [11,13,23]. Others however, have reported no significant (p<0.05) effect of NSAIDs administered prior to [12,15,18] or at the time of the procedure [20,25], on cortisol and/or ACTH, nor acute phase reactants, Hp, SAA and / or CRP [10,19,24].…”
Section: Physiological Measurements Of Pain In Pigletsmentioning
confidence: 99%